2021
DOI: 10.21203/rs.3.rs-691931/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Hydrogen Production from the Air

Abstract: Hydrogen gas (H2) produced by water splitting using renewable energy, namely green hydrogen, is the most promising energy carrier of the low-carbon economy1–6. However, the geographic mismatch between renewables distribution and freshwater availability poses a significant challenge to green hydrogen production7–9. Here, we demonstrate a method of directly producing H2 from the air, namely, capturing freshwater from the atmosphere using hygroscopic electrolyte and converting it to H2 by electrolysis powered by … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 31 publications
0
1
0
Order By: Relevance
“…Furthermore, it has been recently reported that the green energy source hydrogen 74 or hydrogen peroxide 25 can be directly produced from moisture present in air already at low relative humidities. As shown in this work, the colloidal probe method is a suitable platform to study the effects of humidity and may be included in an electrochemical setup to study the effect of mechanical forces on harvesting hydrogen from air.…”
Section: Single-contactmentioning
confidence: 99%
“…Furthermore, it has been recently reported that the green energy source hydrogen 74 or hydrogen peroxide 25 can be directly produced from moisture present in air already at low relative humidities. As shown in this work, the colloidal probe method is a suitable platform to study the effects of humidity and may be included in an electrochemical setup to study the effect of mechanical forces on harvesting hydrogen from air.…”
Section: Single-contactmentioning
confidence: 99%